TRPA1 channel: New kid in the 'neurovascular coupling' town. (June 2021) - Sancho, Maria; Nelson, Mark T.
Abstract: The just-in time delivery of oxygen and nutrients to active brain regions to support function (functional hyperemia; FH) is mediated by not yet fully understood mechanisms collectively referred to as 'neurovascular coupling' (NVC). In a recent publication (eLife 2021) Thakore et al. provide profound mechanistic insight how the capillary endothelial transient receptor potential ankyrin 1 (TRPA1) channel contribute to blood flow control and functional hyperemia in the brain.